2021
DOI: 10.3390/nu13113947
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Interventions for Stress, Anxiety and Depressive Symptoms: A Systematic Review and Meta-Analysis

Abstract: Background. Fasting interventions have shown effectiveness in alleviating stress, anxiety and depressive symptoms. However, no quantitative analysis has been carried out thus far. The objective was to determine the effectiveness of fasting interventions on stress, anxiety and depression and if these interventions were associated with increased or decreased fatigue/energy. Methods. Overall, 11 studies and 1436 participants were included in the quantitative analyses. Results. After limiting analyses to randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 30 publications
2
32
0
2
Order By: Relevance
“…A spiritual element of well-being was seen in our findings through the description of the personal, meaningful, and fulfilling relationship the participants had with God that was reinforced through the act of fasting [ 68 ]. Our findings are in line with findings on Ramadan fasting, as reported in a recent systematic review and meta-analysis on the subject that was found to have a positive influence on stress, anxiety, and depression [ 11 ]. The authors suggest lifestyle factors such as sleep deprivation as possible reasons for these effects [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A spiritual element of well-being was seen in our findings through the description of the personal, meaningful, and fulfilling relationship the participants had with God that was reinforced through the act of fasting [ 68 ]. Our findings are in line with findings on Ramadan fasting, as reported in a recent systematic review and meta-analysis on the subject that was found to have a positive influence on stress, anxiety, and depression [ 11 ]. The authors suggest lifestyle factors such as sleep deprivation as possible reasons for these effects [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with findings on Ramadan fasting, as reported in a recent systematic review and meta-analysis on the subject that was found to have a positive influence on stress, anxiety, and depression [ 11 ]. The authors suggest lifestyle factors such as sleep deprivation as possible reasons for these effects [ 11 ]. Our findings suggest that one strong influence of personal well-being that may contribute to the observed psychological effects could be self-efficacy [ 69 , 70 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The meta-analysis of Berthelot and colleagues selecting randomized controlled trials concluded that fasting interventions, compared to control groups, achieved lower anxiety and depression levels, and it was also useful to decrease body mass index levels [27]. The benefit on weight was also interpreted as relevant since overweight and obesity are common among patients with depressive and anxiety states [28], and this comorbid condition is related to poor therapy response.…”
Section: Diet Intervention On Anxiety and Depressionmentioning
confidence: 99%
“…Further, the association of prolonged fasting with vitality and quality of life is an unexplored domain. Fewer studies have reported fasting to act as a mood enhancer in pain,(8) moderately relieve stress, anxiety, depression(13) and offers rewarding psychological experiences. (14) However, all the previous reports necessitate the need for future randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%